(untitled) (Journal of Education and Development, 2018)
The purpose of this research is to examine the work of the ICT coordinator in the school: How does the coordinator see his role and work, what are the characteristics of the coordinators work and his relationship with supervisors, instructors, principals, teachers and students. The research was conducted in the qualitative method, the tool used to assemble data was a semi-structured interview; Ten ICT coordinators were interviewed from a variety of ages and a wide range of experience in teaching. The study found that ICT coordinators are the key figures in getting the process of implementation moving. The ICT coordinators know the importance of their roles in the schools and feel a great sense of responsibility. The coordinators are responsible for many fields, including the budgetary framework, promoting the teaching-learning process and leading school projects. The coordinators attest to a high level of trust with the principals and a good working relationship with the Ministry of Education’s instructors, so that they have an open channel of dialogue and can consult with them. The work of the coordinator with the teachers consists of the pedagogical and technical aspect that are intertwined and attest to each other’s existence.